Allergen labelling: Current practice and improvement from a communication perspective. Issue 4 (26th January 2021) - Blom, W. Marty; van Dijk, Liselotte M.; Michelsen‐Huisman, Anouska; Houben, Geert F.; Knulst, André C.; Linders, Yvette F. M.; Verhoeckx, Kitty C. M.; Holleman, Bregje C.; Lentz, Leo R.
Abstract: Background: Allergen information on product labels is crucial in food allergy management, though inadequacy in current labelling practices is one of the major causes for accidental reactions upon consuming prepacked food products. Objective: This study analyses current status of communicating allergen information on food labels and provides practical recommendations for improving the label format based on communication theory. Methods: Product labels ( N 288) of seven food categories from private label products and brands were obtained at three retailers in the Netherlands. Information regarding the 14 EU‐regulated allergens was evaluated by the frequency of emphasizing allergens in the ingredient list, use of precautionary allergen labelling (PAL), icons and an allergen information section. Effectiveness of communication was assessed evaluating readability and findability of information on allergens using principles of Gestalt and Cognitive Load theories. Results: As requested by EU regulation 1169/2011, emphasizing allergens in the ingredient list was almost 100%, all other presentations of information on allergens on labels was highly diverse. A separate allergen information section was present on most private label products. This section could, but not necessarily did, repeat allergens from the ingredient list and/or give a PAL. Brands often provided a PAL at the end of the ingredient list. Part of the products displayed an icon at different locations of the label. Label background, a lack of cohesion and variation in location of topics hamper the identification of relevant information on allergens by (allergic) consumers. Recommendations include a standardized order for mandatory and voluntary topics on the label and a separate allergen information section. Conclusion and clinical relevance: Overall, consumers encounter a wide and inconsistent range in ways of presentation of allergen information on labels. Standardization according to basic design principles can improve usability and support safe food purchases for allergic consumers.